2010
DOI: 10.1177/0009922810379039
|View full text |Cite
|
Sign up to set email alerts
|

Changing Overweight Latino Preadolescent Body Mass Index: The Effect of the Parent-Child Dyad

Abstract: Background: Latino children are disproportionately burdened by obesity. Objective: To assess whether body mass index (BMI) change in preadolescents reflected that of their participating parent. Methods: A total of 72 Latino overweight/obese preadolescents (BMI ≥ 85%) and a parent participated in a randomized controlled trial. The intervention group received 5 monthly 60-minute sessions at a recreation center (group physical activity, goal setting). The control group received 2 standard-of-care clinic visits pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
(60 reference statements)
0
26
0
Order By: Relevance
“…Parental and family support, particularly facilitation, or providing opportunities for the child to be physically active, has been found to be highly predictive of PA frequency and duration. 9,35 In this study, results showed that children who talk with their families about healthy food can also positively influence children's PA levels. This highlights the important and influential role of family in supporting children's healthy behavior.…”
Section: Physical Activitymentioning
confidence: 69%
See 3 more Smart Citations
“…Parental and family support, particularly facilitation, or providing opportunities for the child to be physically active, has been found to be highly predictive of PA frequency and duration. 9,35 In this study, results showed that children who talk with their families about healthy food can also positively influence children's PA levels. This highlights the important and influential role of family in supporting children's healthy behavior.…”
Section: Physical Activitymentioning
confidence: 69%
“…Results also showed that children who talk with their families about healthy foods have higher PA duration. Parental and family support, particularly facilitation, or providing opportunities for the child to be physically active, has been found to be highly predictive of PA frequency and duration . In this study, results showed that children who talk with their families about healthy food can also positively influence children's PA levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings are promising, because dietary intake patterns (e.g., eating breakfast daily) is a protective factor against obesity for Latino children (Wojcicki, Schwartz, Jiménez-Cruz, Bacardi-Gascon, & Heyman, 2011). Also overweight/obese Latino preadolescents are more likely to lose weight if their parents also lose weight during that same time period (Barkin, Gesell, Póe, & Ip, 2011).…”
Section: Introductionmentioning
confidence: 99%